PTH-030 Clinic Outcomes For Unselected Patients Reviewed By Doctors And Advanced Nurse Clinicians – Is There Any Difference?. (9th June 2014) - McClements, D; McLindon, J; Chandy, R; Priestley, S; Fox, M; Theis, V; Dobson, J; Bassi, A
Abstract : Introduction: There is a well-established role of specialist nurses in on-going management of chronic diseases in specialist clinics. With the reduction in junior doctor hours, advanced nurse clinicians (ANC) are taking on increasing complex medical roles. We aimed to evaluate the effectiveness of ANC in managing unselected new patients (NP) in the general gastroenterology clinic in a district general hospital. Methods: Analysis was done on 76 consecutive NP seen in the gastroenterology clinic over one week which then generated a further 66 follow appointments over an 18 month follow up period. We compared the direct service costs, diagnosis, outcome and discharge rates for each clinician grade. IBD patients requiring regular follow were excluded from the analysis. Cost analysis was performed using current NHS tariffs for the investigations performed. Results: Forty new patients (53%) were seen by an ANC, 26 (34%) by a consultant gastroenterologist and 10% (13%) by a middle-grade doctor (MG) at the first appointment. Forty referrals were on the 'suspected cancer' pathway, of these 68% were seen by ANC, 13% by a consultant 19% and by MG. Of the 36 non-urgent referrals – 36% were seen by ANC, 55% by a consultant and 9% by MG. The mean number of follow up appointments generated was 1.9 (ANC), 1.8 (consultant) and 2.2 (MG). ANC's ultimately discharged 30 patients (39%), consultants 23 (30%), MG's 7 (9%). Sixteen patients (21%) required long-term follow-up or did not attend. Consultants requested 16 investigations on new patients (0.62 tests/patient) costing £161 per patient, MG 15 investigations (1.5 tests/patients) costing £337/patient and ANC's 50 investigations (1.25 tests/patient) costing £331/patient. Only 1 patient was referred back to clinic having been discharged and this was for a new and unrelated problem. Conclusion: In our hospital, nurse led and doctor led outpatient care was of equivalent effectiveness with no differences in follow-up appointments generated or discharge rates from clinic. During the study period, nurse led care resulted in increased resource use compared with consultant led care – but could be partly explained by the greater proportion of patient seen in the 'suspected cancer' pathway. No adverse outcomes or missed diagnoses were observed over an 18 month follow up period. Our study would support the role of specialist nursing managing unselected patients in gastroenterology clinics. Disclosure of Interest: None Declared.